A novel probability-based diagnostic imaging with weight compensation for damage localization using guided waves. (March 2016) - Liu, Kehai; Ma, Shuyi; Wu, Zhanjun; Zheng, Yuebin; Qu, Xiaoxi; Wang, Yishou; Wu, Wenhua
To avoid direct interpretation of the complicated ultrasonic guided wave signal and the effect of dispersion, probability-based diagnostic imaging is proposed to identify damages for guided wave–based structural health monitoring. However, the probability-based diagnostic imaging algorithm usually requires a relatively large number of actuator–sensor paths to cover the monitoring area. Therefore, a weight-compensated probability-based diagnostic imaging approach is developed to improve the ability of damage localization with higher precision under the same sensor configuration. The weight-compensated probability-based diagnostic imaging algorithm compensates for the weight difference from sensing paths with the unit weight of various positions, inhibited by the path weight difference effect on diagnostic image. The validity of the approach is assessed by identifying damages at different locations with different groups of sensing paths on a stiffened composite panel. Accurate localization results have demonstrated the effectiveness of the developed probability-based diagnostic imaging approach.